Participación de los receptores muscarínicos M2 presentes en el núcleo supraquiasmático sobre la regulación de la ovulación a lo largo del ciclo estral de la rata adulta - Gutiérrez Estrada, Mónica Ingrid (Universidad Autónoma Metropolitana, 2020)
Ovulationis a process regulated by neuroendocrine signals from the hypothalamus, pituitary gland, ovaries, etc.Gonadotropin-releasing hormone (GnRH) is secreted in the hypothalamus, which stimulates the release of gonadotropins in the adenohypophysis. The secretion of GnRH is modulated by various hormones or neurotransmitters that regulate it in a stimulating or inhibitory manner. Several studies have shown that the muscarinic system participates in neuroendocrine mechanisms that regulate ovulation and steroid hormone secretion, which varies depending on the stage of the estrous cycle and the time of day. Ovulation is a periodic process. The pre-secretory secretion of GnRH is regulated by signals that come from the suprachiasmatic nucleus (NSQ). The NSQ receives cholinergic information and there is evidence to show that the cholinergic information that reaches both sides of the NSQ is necessary for the pre-secretory secretion of luteinizing hormone (LH) to induce ovulation. In order to analyze throughout the estrouscycle the participation of the M2 muscarinic receptors (m2AChR)of the Suprachiasmatic nucleus left (NSQ-I) or right (NSQ-D) on ovulation, in the present study the blockade of m2AChR was performed through the use of an antagonist allosteric.For this, female, adult and cyclic rats of the CIIZ-V strain maintained in a photoperiod LD= 14: 10 with water and food ad libitumwere used. To which a guide cannula was inserted directed towards the NSQ-D or NSQ-I. After recovery and presenting three consecutive 4-day estrous cycles, at 7:00 h on the days of estrus, right-handed, right-handed or proestrus, the animals were microinjected with 0.3 μL of a triethiodide solution of galamina (26 nmol) or 0.3 μL of vehicle solution. The animals were sacrificed at 9:00 hfrom the predicted estrous and at the autopsy the number of oocytes released and the rate of ovulating animals (TAO) were quantified. The microinjection of saline solution in the NSQ-I did not modify ovulation. The implantation of the guide cannula or the microinjection of saline solution in the NSQ-D did not change the rate of ovulating animals or the number of oocytes released.In the estrous and proestrusstage, the mass of the uterus of the animals with saline microinjection in the left or right NSQ was smaller than that of the intact group. Microinjection with galamine, in the NSQ-I at the stage ofdiestrus-1 resulted in a decrease in the number of oocytes released with respect to the control group (7.4±2.5 vs. 14.7±0.7). In the proestrus,blockade of the m2AChR receptors resulted in an increase in the number of oocytes released by the left ovary and both with respect to their vehicle group (8.3±0.4 vs. 7.3±1.3; 15.0±0.4 vs. 12.3 ±0.5 respectively).The blockade of the m2AChR receptors in the NSQ-D in the proestrusresulted in the blockage of ovulation with respect to its vehicle group (TAO: 7/9vs. 1/9).In the stage ofdiestrus-2, the animals presented the uterine uterus on the day of sacrifice compared to the control group (5/6vs. 0/6). In rats that do not ovulate, as a result of blocking the m2AChR in the NSQ-D at the stage of the proestrus, the injection of synthetic LHRH induced ovulation,so we suggest that the activation of the m2AChR of the NSQ-D is necessary for thegeneration of the increase in LHRH / LH.Based on the results obtained in this study, we suggest that the m2AChR of the NSQ participate differentially on the neuroendocrine mechanisms that regulate the secretion of GnRH and ovulation, which varies depending on the NSQs studied and the stage of the estrous cycle.; La ovulación es un proceso regulado por señales neuroendocrinas provenientes del hipotálamo, la hipófisis, los ovarios, etc. En el hipotálamo se secreta la hormona liberadora de gonadotropinas (GnRH), la cual estimula en la adenohipófisis la liberación de las gonadotropinas. La secreción de la GnRH es modulada por diversas hormonas o neurotransmisores que la regulan de manera estimulante o inhibitoria. Diversos estudios han mostrado que el sistema muscarínico participa en los mecanismos neuroendocrinos que regulan la ovulación y la secreción de hormonas esteroides, lo cual varía en función de la etapa del ciclo estral y la hora del día. La ovulación es un proceso periódico. La secreción preovulatoria de GnRH es regulada por señales que provienendel núcleo supraquiasmático (NSQ). El NSQ recibe información colinérgicay se tienen evidencias que muestran que la información colinérgica que llega a ambos lados del NSQ es necesaria para la secreción preovulatoria de la hormona luteinizante (LH) para inducir la ovulación. Con el fin de analizar a lo largo del ciclo estral la participación de los receptores muscarínicos M2 (m2AChR) del núcleo supraquiasmático izquierdo (NSQ-I) o derecho(NSQ-D) sobre la ovulación, en el presente estudio se realizó el bloqueo de los m2AChR mediante el uso de un antagonista a lostérico. Para ello, se utilizaron ratas hembras, adultas y cíclicas de la cepa CIIZ-V mantenidas en un fotoperiodo LD=14:10 con agua y alimento ad libitum. A las cuales se les insertó una cánula guía dirigida hacia el NSQ-D o NSQ-I. Después de su recuperación y de presentar tres ciclos estrales consecutivos de 4 días, a las 7:00 h en los días de estro, diestro-1, diestro-2 o proestro, los animales fueron microinyectados con 0.3 μL deuna solución de trietioduro de galamina (26 nmol)o 0.3 μL de solución vehículo. Los animales fueron sacrificadosa las 9:00 hdel estro predichoy en la autopsia se cuantificó el número de ovocitos liberados y la tasa de animales ovulantes (TAO). 2 La microinyección de solución salina en el NSQ-I no modificó la ovulación. El implante de la cánula directriz o la microinyección de solución salina en el NSQ-D no modificó la tasa de animales ovulantes ni el número de ovocitos liberados. En la etapa de estro y proestro, la masa del útero de los animales con microinyección de solución salina en el NSQizquierdo o derecho fue menor que la del grupo intacto. La microinyección con galamina, en el NSQ-I en la etapa de diestro-1 resultó en una disminución del número de ovocitos liberados con respecto al grupo control (7.4±2.5 vs. 14.7±0.7). En el proestro, el bloqueo de los receptores m2AChR resultó en un aumento del número de ovocitos liberados por el ovario izquierdo y por ambos con respecto a su grupo vehículo (8.3±0.4 vs.7.3±1.3; 15.0±0.4 vs. 12.3±0.5 respectivamente). El bloqueo de los receptores m2AChR, en el NSQ-D en el proestro resultó en el bloqueo de la ovulación con respecto a su grupo vehículo (TAO: 7/9vs.1/9). En la etapa del diestro-2, los animales presentaron el útero balonado el día del sacrificio a comparación del grupo control (5/6vs. 0/6) En ratas que no ovulan, resultado del bloqueo de los m2AChR en el NSQ-D en la etapa del proestro, la inyección de LHRH sintética indujo la ovulación, por lo que sugerimos que la activación de los m2AChR del NSQ-D es necesaria para la generación del aumento preovulatorio de LHRH/LH. Con base en los resultados obtenidos en este estudio, sugerimos que los m2AChR del NSQ participan de manera diferencial sobre los mecanismos neuroendocrinos que regulan la secreciónde GnRHy la ovulación, lo cual varía en función del NSQs estudiado y de la etapa del ciclo estral.